Honest versus Misleading Certification. Issue 2 (2nd February 2017) - Mahenc, Philippe
Abstract : This paper questions the honesty of third‐party certification in the market for a good whose environmental quality is not observable by consumers. The certifier maximizes a weighted sum of its own revenue and social welfare. The higher the relative weight placed on revenue, the stronger the certifier's incentive to mislead consumers. Certification is analyzed as a costly signaling mechanism that, besides displaying labels, transmits information through market prices. Honest certification requires that prices credibly signal environmental quality to prevent cheating. I show that certification can only be honest when the certifier is driven more by social welfare than by profit. In the reverse case, the certifier cannot help jamming the price signal, thereby granting unreliable labels.